SERIAL VERB CONSTRUCTION IN BALINESE (SYNTACTIC AND SEMANTIC ANALYSIS) - Mas Indrawati, Ni Luh; Artawa, Ketut; Putra Yadnya, Ida Bagus; Sedeng, I Nyoman (e-Journal of Linguistics; Vol. 6. Januari 2012 No. 1)
Serial verb construction (SVC) is a construction where more than one verbs occur in a clause without any overt markers of  subordinator or coordinator. SVC is a common fenomenon in isolative languages which lack morphological markers for sintactic processes.  However, in the use of Balinese, which is  rich in morphological markers, SVC are common fenomena.  This research attempts to analyse the typological characteristics of SVC in Balinese, to describe the types of SVC in Balinese viewed from the structure of events which forms the SVC, to analyse the constituent merging strategies in clauses containing SVC. This research applies decriptive-qualitative approach, by combining analitic and introspective methods. The data source of this research was 50 short story texts taken from Sastra slot in “Bali Orti”, weekly newspaper of Bali Post, completed with spoken texts, obtained by applying direct observation technique. The data was descriptively and analitically analysed by using the deductive-inductive-deductive approach. The theories applied in analysing SVC in Balinese were: tipological, semantic cognitive, and sintactic theories. The result shows that typologically, SVCs in Balinese had three characteristics that is: phonetic, morphosyntactic, and semantic characteristics. Viewed from the integration of events in Balinese SVCs, it could be proved that SVCs in Balinese express a single macro-event and could be classified into two  types, they were: component SVC and narative SVC. Syntactically SVCs in Balinese were biclausal constructions, some were monoclausal, and successive clauses.
Keywords: SVC, typology, event integration, constituent merging.